Related Posts

This Post Has 4 Comments

  1. -8x-9y

    Step-by-step explanation:

    Hey There!

    So basically this problem is asking you to simplify this expression using distributive property

    The first step would be to distribute 7 into what is inside the parenthesis (2x and -3y)

    2x*7=14x

    -3y*7=-21y

    so now we have 14x-21y + 4(3y-5x)

    the next step would be to distribute 4 to what is inside the parenthesis (3y and -5x)

    4*3y=12y

    4*-5x=-20x

    so now we have 12x-21y-20x+12y

    the final step is to combine like terms

    12x-20x=-8x

    -21y+12y=-9y

    so the simplified version of 7(2x - 3y) + 4(3y - 5x) is -8x-9y

Leave a Reply

Your email address will not be published. Required fields are marked *